2004
DOI: 10.1590/s1679-62252004000300005
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, abundance and morphometry of Atlantoraja cyclophora (Regan, 1903) (Elasmobranchii: Rajidae) in southern Brazil, Southwestern Atlantic

Abstract: A total of 459 individuals of Atlantoraja cyclophora were captured along the Rio Grande do Sul coast between latitudes 30°40'S and 34°30'S. Two surveys were performed, in the winter 2001 and in the summer/autumn 2002, using bottom-trawl between the depths of 100 and 600 m. This species occurred between 100 and 300 m deep, without significant differences in the frequency of occurrence and abundance (CPUE; kg/hour) between latitudes, depth and seasons. The sex ratio was not significantly different from 1:1 in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Females also reached larger size than males, as observed in other studies with A. cyclophora (ODDONE & VOOREN 2004, ODDONE et al 2008. Skates were more abundant in the summer (Jan-Feb-Mar 06 and Jan-Feb-Mar 07).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Females also reached larger size than males, as observed in other studies with A. cyclophora (ODDONE & VOOREN 2004, ODDONE et al 2008. Skates were more abundant in the summer (Jan-Feb-Mar 06 and Jan-Feb-Mar 07).…”
Section: Discussionsupporting
confidence: 82%
“…Skates were more abundant in the summer (Jan-Feb-Mar 06 and Jan-Feb-Mar 07). Summer is the season of greatest upwelling of the South Atlantic Central Water (SACW), which generates the oceanographic conditions favored by this species (ODDONE & VOOREN 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others, however, are not well understood and their utility, if any at all, is not obvious. For example, sexually dimorphic pectoral fins have been cited in Neoraja stehmanni , Raja straeleni , and Raja miraletus (Ebert et al ) as well as Atlantoraja cyclophora (Oddone and Vooren ). In all instances, males took on a “bell‐shaped” body form at maturity (Ebert et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Differences between sexes for the L T ‐ W D relationship may reflect a sexual dimorphism, clearly visible in the form of the disc, with males having a bell‐shaped body. Sexual dimorphism in W D may occur in species with sexual differences in length‐width relationships (Ebert et al, ) and has been observed in other rajoids (Oddone & Vooren, ; Orlov & Cotton, ). Such dimorphism may be related to the onset of maturity, since it becomes evident in developing and adult individuals (Martinez et al, ).…”
Section: Discussionmentioning
confidence: 91%